GRB2 nucleates T cell receptor–mediated LAT clusters that control PLC-γ1 activation and cytokine production - Bilal, Mahmood Y.; Houtman, Jon C. (Frontiers in Immunology, 2015)
GRB2 is a ubiquitously expressed adaptor protein required for signaling downstream of multiple receptors. To address the role of GRB2 in receptor-mediated signaling, the expression of GRB2 was suppressed in human CD4+ T cells and its role downstream of the T cell receptor was examined. Interestingly, GRB2 deficient T cells had enhanced signaling from complexes containing the TCR. However, GRB2 deficient T cells had substantially reduced production of IL-2 and IFN-γ. This defect was attributed to diminished formation of LAT signaling clusters, which resulted in reduced MAP kinase activation, calcium flux and PLC-γ1 recruitment to LAT signaling clusters. Add back of wild-type GRB2 but not a novel N-terminal SH3 domain mutant rescued LAT microcluster formation, calcium mobilization, and cytokine release, providing the first direct evidence that GRB2, and its ability to bind to SH3 domain ligands, is required for establishing LAT microclusters. Our data demonstrate that the ability of GRB2 to facilitate protein clusters is equally important in regulating TCR-mediated functions as its capacity to recruit effector proteins. This highlights that GRB2 regulates signaling downstream of adaptors and receptors by both recruiting effector proteins and regulating the formation of signaling complexes.